Teori jaringan sosial dan perannya dalam pemberdayaan komunitas - purnama, silvia gadis (Maliki Interdisciplinary Journal, 2025)
Social networks refer to the relationships between individuals or groups that are connected through communication, cooperation, and information exchange. Using a descriptive qualitative approach, this article explores how social networks strengthen social capital and accelerate community transformation. Findings show that social networks are essential for expanding access to information, building trust, enhancing social solidarity, and increasing civic participation in empowerment programs. Nonetheless, their implementation faces challenges such as limited local capacity, low engagement, and infrastructure issues. Strategies such as training, institutional collaboration, and asset-based approaches are recommended to address these issues.